Liquid-Liquid Extraction of Palladium(II) from Hydrobromic Acid Media by Hexadecylpyridinium Bromide - SALIMI, Shabnam; JABBARI, Ali; ALIZADEH, Naader (Analytical Sciences, 2002)
A simple and rapid liquid-liquid extraction of palladium has been studied involving ion-pairing of bromocomplexes of palladium(II) with hexadecylpyridinium bromide (HDPB) dissolved in chloroform. The stoichiometry and distribution of (HDP)2PdBr4 between the aqueous and organic phase was investigated by spectrophotometric mole ratio method. The extraction efficiency of palladium(II) by HDPB was studied as a function of several variables: acid, salt, surfactant concentration and equilibrium time. The results showed that PdBr42- extraction could be explained by assuming the formation of (HDP)2PdBr4 complexes in the aqueous solution and transfer to organic phase. The extraction was fast and the shaking time was only a few min. The average recovery of palladium(II) from an aqueous solution containing 10 µg/ml of analyte was 99% with an RSD% of 0.95. The percentage recovery of 0.2 µg/ml palladium(II) was 96%.